Chemical Characterisation of Inorganic Profile of Wine Obtained by Alternative Vinification in Comparison with Traditional One - Nicola Mercanti; Ylenia Pieracci; Monica Macaluso; Angela Zinnai; Olivier F. X. Donard; Véronique Vacchina (Foods)
The complex dynamics between oxygen exposure, sulphur dioxide use, and wine quality are of the utmost importance in modern winemaking. While SO2 acts as an effective antiseptic and antioxidant, its excessive use raises health concerns, prompting stricter regulations (Council Regulation EC No. 1493/1999; Commission Regulation EC No. 1622/2000) and increasing interest in natural alternatives. In this context, Bioma SA developed plant-based additives derived from vineyard by-products rich in phenolic compounds to replace SO2 in vinification. This study has evaluated the impact of these additives on the inorganic elemental composition of Sangiovese wines, comparing traditional sulphite-based vinification with the Bioma-based alternative. Using triple quadrupole ICP-MS, 23 elements were quantified and analysed via ANOVA and principal component analysis (PCA). The results revealed significant effects of the vinification protocol and ageing method on key elements such as Mn, Rb, Sr, Ni, and As. Importantly, all toxic elements, Pb (≤5.9 µg/L), Cd (≤0.3 µg/L), and As (≤12.1 µg/L), remained well below EU safety thresholds. PCA further highlighted distinct elemental profiles between traditional and Bioma wines. These findings confirm that Bioma additives enable the production of wines with reduced sulphur content and compliant elemental safety, supporting their potential as sustainable, health-conscious alternatives in modern oenology.